2007
DOI: 10.1002/pbc.21277
|View full text |Cite
|
Sign up to set email alerts
|

Loss of antibody titers and effectiveness of revaccination in post‐chemotherapy pediatric sarcoma patients

Abstract: Our findings suggest that post-chemotherapy patients may need to be revaccinated against certain vaccine-preventable diseases including hepatitis B, tetanus, varicella, polio, measles, mumps, and rubella. Larger studies need to be performed to establish guidelines for revaccinating post-chemotherapy pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…There are well-established recommendations for reimmunizations after HSCT, but no consensus still exists regarding whether reimmunizations are necessary after standard chemotherapy, and when such reimmunizations should take place (22, 23). A few cohort studies were published to address changes of antibody titers and response to booster vaccine after chemotherapy (24-26). On the basis of our data, we agree with the strategy of reimmunizing each patient who completed chemotherapy only, as well as HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…There are well-established recommendations for reimmunizations after HSCT, but no consensus still exists regarding whether reimmunizations are necessary after standard chemotherapy, and when such reimmunizations should take place (22, 23). A few cohort studies were published to address changes of antibody titers and response to booster vaccine after chemotherapy (24-26). On the basis of our data, we agree with the strategy of reimmunizing each patient who completed chemotherapy only, as well as HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The defects in immunological functioning caused by intensive chemotherapy may adversely affect the immune memory so that it may not be protective in childhood cancer patients. [18] Despite being vaccinated as part of the EPISA, patients have acquired HBV in the paediatric oncology unit at SBAH. [7] Previous studies have shown that HBV immunity declines with age.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors agree that the interval time of 6–12 months is adequate to achieve a sufficient immune recovery that, in turn, has a key role in determining the response to vaccination [14, 20, 83, 8588, 91, 95, 96], but some studies have shown good results after reimmunization with inactivated vaccines already at 3 months [87]. …”
Section: Resultsmentioning
confidence: 99%